Analisis Tingkat Kerawanan Banjir di Kecamatan Koto Tangah, Kota Padang - Isra Iza Mahendra; Dwi Marsiska Driptufany; Dwi Arini (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
The research area is prone to flooding, which could potentially result in losses for the people of the research area. Based on this, it is important to map flood-prone areas, as a form of flood disaster mitigation effort to reduce the level of flood risk. Hazard mapping is an important stage in the process of disaster risk identification and analysis. Mapping flood-prone areas can use various methods or approaches. Approaches that can be used for assessing or mapping flood hazards are the geomorphological approach and community participation. This type of research is quantitative descriptive, namely a type of investigation that explains or explains a problem. Descriptive studies aim to explain populations, situations or phenomena accurately or systematically. Mapping flood hazards in the Koto Tangah District, Padang City. From the results of the analysis of the level of flood vulnerability above, the relationship between this research is that rainfall is too high and low river beds cause water to overflow into lowlands, causing the level of flood vulnerability to increase as time goes by. So The results obtained from the analysis of Flood Hazard Area Mapping are the area of ​​Koto Tangah sub-district is 22.017,43ha, by getting the level of non-prone areas with an area of ​​10.203.16ha, the level of less-prone areas with an area of ​​4.714.168ha, the level of vulnerable areas with an area of ​​3.990.458ha, the level of very vulnerable area with an area of ​​1.893,630ha. Koto Tangah District, Padang City has five levels of danger zones for flooding, based on the results of the parameter data used. Each parameter used greatly influences the level of flood risk in Koto Tangah District, Padang City, namely river buffer, land use, land height, land slope, soil type and rainfall. From the creation of flood prone levels in Koto Tangah sub-district, Padang city, areas with a very high risk of flooding are 10.68% with an area of ​​1892,630 ha, areas with a danger level of flood prone are 14.68% with an area of ​​3990,458 ha, areas with Kuang's flood-prone level is 21.40% with an area of ​​4714,168 ha, the area with a flood-safe level is 46.32% with an area of ​​10,203.16 ha.